Strategi Penerapan dan Implementasi Pembiayaan Murabahah di UPK Eks-PNPM Kabupaten Pidie - Rahmad, Rahmad; Nazaruddin A Wahid; Muhammad Yasir Yusuf (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the application of murabahah financing in the former PNPM Unit of Kabupaten Pidie and evaluate the implementation of Sharia economic principles in murabahah financing. It is a qualitative-normative field study focusing on the implementation of murabahah financing in UPK Kabupaten Pidie. The normative approach is employed to formulate proportional legal concepts in murabahah financing, while the juridical approach analyzes relevant legal regulations. The historical approach investigates the concept of murabahah by past Islamic jurists, and the empirical approach analyzes the implementation of murabahah financing in UPK as well as its underlying factors. The research findings reveal that the application of murabahah in UPK Eks-PNPM Kabupaten Pidie does not reflect a commitment to building an economy aligned with Sharia principles. In practice, murabahah is not used as a financing tool prioritizing transparency, where the presence of goods and profit margins should be clearly stated. UPK Eks-PNPM should take initiatives to realize a murabahah model that aligns with Sharia principles, as part of efforts to promote economic justice and Islamic business ethics. Overall, the implementation of Sharia economic principles in murabahah financing at UPK Eks-PNPM not only ensures Sharia-compliant financial systems but also contributes to comprehensive community empowerment. By emphasizing Islamic values in every aspect of economic activities, UPK Eks-PNPM establishes a sustainable model in line with the principles of social and economic justice in Islam.